Breaching Barriers: Microplastic Translocation into Human Body Through Food and Implications for Neurodegeneration - Chman Shahzadi; Lisa Aielli; Erica Costantini; Marcella Reale; Piero Di Carlo (Current Pollution Reports, 2025)
Introduction Plastics are ubiquitous in modern life, widely used in food containers, packaging, and textiles. Micro- and nano plastics (MNPs), originating from environmental sources, agricultural practices, and packaging materials, can infiltrate the food chain, posing potential health risks. Results Studies have demonstrated that MNPs leach into food from both the surrounding environment and plastic packaging, with factors such as low pH and elevated temperatures significantly enhancing their release. Upon ingestion, these particles traverse biological barriers, enter systemic circulation, and accumulate in organs, including neurons and brain regions, where they disrupt normal biological processes. Mechanistically, MNPs induce neuronal damage through oxidative stress, endoplasmic reticulum stress, lysosomal dysfunction, altered proinflammatory gene expression, and neurotoxicity, which can trigger pyroptosis and progressive neuronal loss, ultimately contributing to neurodegeneration. Methods This systematic review synthesizes studies from the past fifteen years, documenting the presence of MNPs in food and beverages, quantifying their levels, and linking their occurrence to environmental plastic pollution and packaging materials. It also highlights the role of MNPs in neurotoxicity, elucidating potential biological mechanisms leading to neuronal damage, and their possible association with neurological disorders such as cognitive impairment, Alzheimer’s disease, and Parkinson’s disease. Conclusion These findings underscore the urgent need for further research to track MNPs within the nervous system and to implement mitigation strategies aimed at reducing MNP contamination across the food supply chain. Graphical Abstract

Improved osteogenic differentiation by extremely low electromagnetic field exposure: possible application for bone engineering - Erica Costantini; Guya Diletta Marconi; Luigia Fonticoli; Lisa Aielli; Oriana Trubiani; Thangavelu Soundara Rajan; Jacopo Pizzicannella; Marcella Reale; Francesca Diomede (Histochemistry and Cell Biology, 2022)
Human periodontal ligament mesenchymal stem cells (hPDLSCs) are a promising cell type model for regenerative medicine applications due to their anti-inflammatory, immunomodulatory and non-tumorigenic potentials. Extremely low-frequency electromagnetic fields (ELF-EMF) are reported to affect biological properties such as cell proliferation and differentiation and modulate gene expression profile. In this study, we investigated the effects of an intermittent ELF-EMF exposure (6 h/day) for the standard differentiation period (28 days) and for 10 days in hPDLSCs in the presence or not of osteogenic differentiation medium (OM). We evaluated cell proliferation, de novo calcium deposition and osteogenic differentiation marker expression in sham and ELF-EMF-exposed cells. After ELF-EMF exposure, compared with sham-exposed, an increase in cell proliferation rate ( p < 0.001) and de novo calcium deposition ( p < 0.001) was observed after 10 days of exposure. Real-time PCR and Western blot results showed that COL1A1 and RUNX-2 gene expression and COL1A1, RUNX-2 and OPN protein expression were upregulated respectively in the cells exposed to ELF-EMF exposure along with or without OM for 10 days. Altogether, these results suggested that the promotion of osteogenic differentiation is more efficient in ELF-EMF-exposed hPDLSCs. Moreover, our analyses indicated that there is an early induction of hPDLSC differentiation after ELF-EMF application.

Blood natural killer activity is reduced in men with occupational stress and job insecurity working in a university - Paolo Boscolo; Angela Di Donato; Luca Di Giampaolo; Laura Forcella; Marcella Reale; Vincenzo Dadorante; Francesca Alparone; Stefano Pagliaro; Maria Kouri; Andrea Magrini; Emanuela Fattorini (International Archives of Occupational and Environmental Health, 2009)

MCP-1 and MIP-2 expression and production in BB diabetic rat: Effect of chronic hypoxia - Cacchio Marisa; Isabella Lucci; Camillo Di Giulio; Giuseppina Bianchi; Alfredo Grilli; Antonia Patruno; Marcella Reale (Molecular and Cellular Biochemistry, 2005)

Inhibition of MCP-1 and MIP-2 transcription and translation by mimosine in muscle tissue infected with the parasite Trichinella spiralis - Pio Conti; Stavros Frydas; Marcella Reale; Renato C. Barbacane; M. Di Gioacchino; M. Felaco; A. Trakatellis (Molecular and Cellular Biochemistry, 2002)

Impact of extremely low frequency electromagnetic fields on CD4 expression in peripheral blood mononuclear cells - Mario Felaco; Marcella Reale; Alfredo Grilli; Maria A. De Lutiis; Renato C. Barbacane; Silvano Di Luzio; Pio Conti (Molecular and Cellular Biochemistry, 1999)

Infra-red laser irradiation enhances interleukin-1 receptor antagonist, increases 3H-thymidine incorporation and the release of [3H]arachidonic acid in human monocytes - Marcella Reale; Claudio Orso; Maria Luisa Castellani; Renato Carmine Barbacane; Fernanda Cristina Placido; Ettore Porreca; Concetta Di Febbo; Ivana Cataldo; Demetrio Vacalis; G. Anogianakis; A. Trakatellis; Pio Conti (Molecular and Cellular Biochemistry, 1997)